أوضاع الزراعة الديمية لمحصولي القمح والشعير في العراق: إشكالية الجفاف للموسم 1999/1998 - حالة إستعراضية - الدكتور باسل كامل دلالي,; الدكتور سالم توفيق النجفي, (PROSPECTIVE RESEARCHES, 2023)
Drought is being considered one of the uncertainty phenomena that characterized rainy agriculture. Agriculture in Iraq has witnessed this phenomena for the producing season 1998-1999 especially in subguaranteed and unguaranteed areas. The lands included of drought have been used to produce both barley and wheat products of the product incomes with the value of (50605) million I.D. both seeds and fertilizers have shared by 30.0% and 16.5% respectively whereas labour, technology and land rent have shared by 53.5%. Damages and losses have been estimated due to both unharvested products about (67180) million I.D. both wheat and barley have participated by 64% and 46% respectively. This has its impact economically upon the Iraqi food security and distributing the agrarian income in Nineveh province as well as other negative economic consequences.